Assembly of a coordination polymer with sulphate-capped pentamolybdate units and copper: synthesis, structure, magnetic and catalytic studies. Issue 18 (27th April 2022) - Gupta, Yesleen; Zaidi, Zakiullah; Mehta, Sakshi; Chandewar, Pranay R.; Kumar, Nikhil; Paul, Avijit K.; Shee, Debaprasad; Mondal, Abhishake; Sorokhaibam, Laxmi Gayatri; Banerjee, Abhishek
Abstract : The coordination polymer [Cu II (C5 H5 N)4 ]3 [MoVI5O15 (SO4 )2 Cu II (C5 H5 N)3 (DMF)(H2 O)][MoVI5O15 (SO4 )2 ]·2DMF, with a double-chain structure, exhibits unique nanoporous properties and catalytic activity towards oxidative desulfurization of model oil. Abstract : A new coordination polymer based on the sulphate-capped pentamolybdate unit has been synthesized from the reaction of Mo3 S7 Br6 2− with copper(ii ) bromide and pyridine, in DMF. The as-synthesized compound, formulated as [Cu II (C5 H5 N)4 ]3 [MoVI5O15 (SO4 )2 Cu II (C5 H5 N)3 (DMF)(H2 O)][MoVI5O15 (SO4 )2 ]·2DMF (1 ), crystallizes in the monoclinic space group of P 21 / c . This compound has a one-dimensional double-chain coordination polymeric structure, composed of the pentameric MoVI5O15 (SO4 )2 and the Cu II (C5 H5 N)4 units, and has been characterized in the solid-state with single-crystal and powder X-ray diffraction, infrared and optical spectroscopy, as well as thermal and magnetic studies. Due to its unique arrangement, the compound is observed to be nanoporous in nature, occupied by a co-crystallized DMF molecule. Surface area measurements confirm the presence of nano-sized pores within the compound. Variable temperature P-XRD studies show the framework to be stable up to a temperature of at least 100 °C. Due to its rigid framework and the presence of nano-sized pores, the compound was extensively studied as a catalyst for oxidative desulphurization of model oil and commercial diesel. The compound not only shows excellent performance for the removal of recalcitrant sulphur components, such as dibenzothiophene (DBT) in fuel oil (∼100% removal), but is also observed to show excellent turn-over-numbers, regeneration, and reproducibility during the catalytic process.